The Influence Of Parents' Economic Conditions On The Cognitive Thinking Ability Of Social Studies Students At Smp Negeri 19 Kupang City - Tosi, Esry Defriana; Rato , Flafius S. (Jurnal Indonesia Sosial Sains, 2025)
This study aims to examine the influence of parents' economic conditions on students' cognitive abilities in Social Studies (IPS) at SMP Negeri 19 Kota Kupang. The research uses a quantitative approach with a linear regression method. A total of 56 students from a population of 126 eighth-grade students were selected using proportional random sampling. Data were collected through observation, tests, and questionnaires, and analyzed using linear regression and t-tests. The results show a significant influence of parents' economic conditions on students' cognitive abilities, with a significance value of 0.002 < 0.05. Parents' economic conditions contribute 44% to the variation in students' cognitive performance. These findings indicate that better parental economic conditions correlate with higher student cognitive abilities.